Does Altmetric Attention Score Correlate with Citations of Articles Published in High CiteScore Journals: Analysis of Three Open Access LIS Journals - Basumatary, Bwsrang; Tripathi, Manorama; Verma, Manoj Kumar (DESIDOC Journal of Library & Information Technology, 2023)
In the ever-evolving landscape of scholarly communication, research impact assessment has expanded beyond traditional citation metrics. Altmetrics, which encompass a wide range of online indicators like social media mentions, downloads, and blog posts, provide insights into the broader societal engagement with scholarly works. This study explores the relationship between Altmetric Attention Scores (AAS) and traditional citation metrics within the Library and Information Sciences (LIS) domain, focusing on high CiteScore open-access journals. The study collected bibliographic data of top 100 articles from Dimensions.ai database that were published between 2013 and 2022 and assesses the alignment between scholarly recognition and online engagement. The top 100 articles were selected based on highest AAS to focus on the most influential and widely-discussed research in order to provide a comprehensive overview of current trends and impactful findings in the field. The dissemination pattern of research highlights across various social web platforms is examined, shedding light on the diverse channels through which research reaches audiences. Correlation analysis reveals a weak and statistically insignificant connection between AAS and citations for the studied journals, emphasising the nuanced nature of scholarly impact in today’s digital landscape. The findings underscore the need to consider both traditional and alternative metrics when evaluating research influence and engagement in the evolving scholarly communication paradigm of the digital age. While this study is confined to specific journals within the LIS domain, its insights contribute to a deeper understanding of the multifaceted nature of research impact assessment.